Distal fibular excision: A review of the literature and presentation of our reconstruction technique case series. (March 2021) - Lamb, Ashley; Mueller, Joseph; Levy, Ezra; Hobbs, Janet L.; Brien, Earl
Highlights: Distal fibula resection is a procedure that has been described as early as 1938 for the treatment of neoplastic lesions. Medial instability of the elbow can be traced back to the literature as far as 1946. The described technique can preserve long-term tibiotalar congruity and stability, allowing these patients to return to near normal function. Abstract: Distal fibula resection is a procedure that has been described as early as 1938 for the treatment of neoplastic lesions. There have been several techniques described for the reconstruction of the remaining tibiotalar joint to prevent deformity and maintain as much function as possible. While these reconstruction techniques provide an option for limb salvage with the removal of disease, patients are faced with chronic pain, loss of function, valgus instability, need for long term orthosis, early arthritis, or significant morbidity related to proximal dissection and disruption of native knee anatomy. We present a case series that is compliant with PROCESS 1 criteria to demonstrate the effective treatment with distal fibular excision and a reconstruction technique inspired by the original Tommy John procedure of the elbow. This procedure has allowed these two patients long-term stability of the ankle, maintenance of full function, and high levels of function. The first case is a 23-year-old female with high-grade osteosarcoma and the second patient is a 19-year-old female with Ewing sarcoma. Details of the procedure as well as clinical and radiographic follow up of these two patients will be described.